PSA Aquagenic Urticaria (Water Allergic) - Arina Natasya Ab Halim; Dr. Myzan Noor (Journal of Computing Technologies and Creative Content, 2022)
A public service announcement (PSA) is a new form of communication that is used to increase public awareness and enhance public perceptions, views, and even actions around a specific problem. These messages can be instructive, inspiring, or even startling in order to elicit emotion and action. For example, raising knowledge about mankind, history, and uncommon diseases, among other things. This study employs the Addie model, which includes analysis, design, development, implementation, and evaluation. The goal of this study is to figure out how to make it easier for people to grasp the main reasons for Aquagenic Urticaria (AU) or Water Allergic.